Structure-based virtual screening for the inhibition and clearance of amyloidosis by small molecules as pharmacological chaperones - Fantao Sun; Jinrong Yang; Jialu Sun; Yu Liu; Lei Zhang; Jin-wu Yan (European Journal of Medicinal Chemistry Reports, 2023)
The accumulation, processing and toxicity of Aβ can be affected by interacting with transthyretin (TTR). We obtained 31 compounds with different structures by virtual screening based on protein structure. Among them, compound 11 inhibited acid-induced TTR protein amyloid fibrils by 75.57 ​± ​11.27%, inhibited Aβ amyloid fibrils by 68.55 ​± ​0.81%, and promoted depolymerization of Aβ fibrils by 109.2 ​± ​7.9%. Surprisingly, this molecule, as a pharmacological chaperone of TTR/Aβ, bound to TTR and Aβ to form a ternary complex that promoted Aβ phagocytosis by microglia and attenuated Aβ neurotoxicity. These results together suggest that formation of the ternary complex [TTR+11] +Aβ may become a viable therapeutic approach for AD treatment.